Feminist Pedagogy as Interruption of Domination: Case Studies of Graduate Studies KWG UI & IKG UIN Kalijaga - Dewi Candraningrum; Anita Dhewy (Yayasan Jurnal Perempuan, 2016)
Feminist pedagogy explicitly documented equal and inclusive interactions that is aware of the existence of the other in the text and practice of knowledge. Feminist pedagogy is not a tool or collection strategy, but it is a philosophy which links the theory of teaching and learning that putting feminism in its central dynamics. It accepts to be appreciated, criticized, and fought as a form of knowledge dynamics. First, it did the work of resistance against hierarchy and domination. Second, it used the experience as a source of knowledge. Third, it made a transformation and realization in arrays of critical ways. This paper investigates two studies centers: Gender Studies Graduate Program of UI (later shortened as KG UI), which was established in 1990; and Islam & Gender Study UIN Kalijaga (later shortened as IKG UIN YK) which was established in 2015. In-depth interviews are mainly done to the founders of the graduate school at the two universities, lecturers and students.